Quantificação de Pratylenchus brachyurus em genótipos de soja (Glycine max L) Merril, em Tupirama/TO - Souza, Renata Aparecida de (2009)
This study analyzed the reaction of soybean lines to the nematode Pratylenchus brachyurus. The reaction of 70 genotypes, including commercial cultivars and under development by Pioneer Seeds were evaluated in a field experiment conducted in the city of Tupirama-TO. The major objective was to select tolerant or resistant cultivars to Pratylenchus brachyurus. Resistance, or tolerance, was determined by observing reproductive parameters in the plant root system, and geospatial aspects of the test and of the root system with a rating scale, developed during the work. The experimental design was completely randomized, with six replicates. The evaluation of the test and processing of soil and root samples to estimate the nematode population was done 80 days after planting. The results showed that all soybean cultivars evaluated hosted Pratylenchus brachyurus, but to different degrees. A smaller reproduction degree of P. brachyurus was observed in the lines of the Breeding Program of Pioneer Soybean Seeds, PHI022, PHI007, PHI027 and PHI031 and other lines us P99R01, M8352RR, Doko RC, P98R31 and PI200490 with final population = 0.71 nematodes g-1 of roots. It not possible to establish any correlations between the parameters evaluated: development of root and shoot and final nematode population.